The simulation of current - voltage characteristics and fabrication process for single electron transistor (set) - Le , Hoàng Minh (Journal of Technical Education Science, 2016)
Calculation and simulation of SET (Single Electron Transistor) are the first steps to determine necessary parameters for a SET structure, and also very important before the fabrication process. Structure of SET has to satisfy criteria about the suitable current and voltage. Accordingly, simulation of SET structure takes a key-role and must be invested fully in order to support the fabrication more advantageously save materials significantly, produce highly practical products having commercial value. In this research, the authors used non-equilibrium Green's function method to computer transport function of charges, the simulation of current-voltage (I-V) characteristics was programmed by using graphic user guide (GUI) in Matlab and the software Intellisuite in design of fabrication process for SET.